Nilai Gizi Bolu Kukus dan Cookies Labu Kuning (Cucurbita moschata Durch) Berbahan Formula Modisco - Sugeng Maryanto; Dyah Kartika Wening (Media Gizi Kesmas, 2023)
Background: Processed products as popular snacks in Indonesia are steamed cakes and cookies. Various recipes were developed to complement and increase the nutritional value of processed products. One way is to make a formulation of steamed cakes and cookies based on the modisco formula with the addition of local food, pumpkin. Modisco is a food additive in liquid form with a composition of full cream milk, granulated sugar, margarine. The new product innovation of processed steamed cakes and cookies is fortification of modico with the addition of pumpkin as a local food. Objectives: This study conduct to describe the nutritional value of processed product formulations for steamed cakes and cookies which have been fortified with modico were used pumpkin as a local food. Methods: This study used an experimental design, divided into two groups, there are the steamed cakes group and the cookie group based on the modico formula for fortification which has been modified together with local pumpkin food. The variables measured for content analysis were the nutritional value of macronutrients, there are protein, fat, carbohydrate, and fiber. Data analysis was carried out by describing the nutritional value of steamed cakes and cookies modisco formula made from pumpkin.   Result: The processed steamed cakes based on the modisco formulation with the addition of pumpkin per 100 grams were contains 9.25 grams of protein, 11.21 grams of fat, 32.50 grams of carbohydrates and 2.18 grams of fiber, with an energy of 268.62 kcal. The processed cookies based on the modisco formulation with the addition of pumpkin per 100 grams were contain 7.92 grams of protein, 16.7 grams of fat, 61.79 grams of carbohydrates and 2.49 grams of fiber, with an energy of 426.34 kcal. Conclusion: The processed cookies based on the modisco formulation with the addition of pumpkin were contains higher energy, carbohydrates, compared to processed steamed cakes.